Showing Off or Laying Low? The Economics of Psych-outs - Philipp Denter; John Morgan; Dana D. Sisak (Tinbergen Institute, 2018)
We study situations where a new entrant with privately known talent competes with an incumbent whose talent is common knowledge. Competition takes the form of a rank-order tournament. Prior to the competition, the newbie can "show off," i.e., send a talent revealing costly signal. We find that incentives to show off can go in either direction—more talented types may wish to mimic less talented ones or the reverse, depending on the newbie's talent distribution compared to the one of the incumbent. In equilibrium though, showing off occurs only when the newbie is exceptionally talented compared to the incumbent. Surprisingly, showing off occurs to the benefit of both parties; the newbie benefits for obvious reasons, the incumbent by economizing on wasted effort when overmatched. We use our findings to study the broader consequences of showing off, which is discouraged in many cultures through implicit social norms. We show that norms against showing off raise total effort but worsen talent selection, and are thus appropriate only when effort is society's main concern.
Keywords: D23; D83; M52; 330; Showing Off; Contests; Norms